Bahasa Inggris - Bagus Roni Setiawan; Efriyani Sumastuti; Shofif S Akbar (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The essence of this research aims to decide the impact of HR Competence and Work Discipline on MSME performance with Inspiration as a mediator in Semarang City. This research itself was conducted at the Culinary MSME of Semarang City. The research method uses quantitative research. The respondents obtained were 539 respondents who were Culinary MSME business actors in Semarang City. The testing strategy utilized simple random sampling with a total sample of 241 respondents. The analysis technique used is multiple linear regression analysis, for data processing utilizing the assistance of SmartPLS 3.0 SEM software. The research results obtained that HR Competency and Work Discipline meaningfully a positive and significant effect on Motivation with a T-Value > 0.01. Motivation affects positive and significant MSME performance with a T-Value > 0.01.